Exploring the Entrepreneurial Climate and Attributes of Agripreneurs and its Determinants - Gupta, Sanjay Kumar; Manjeet Singh Nain; Rashmi Singh; Jyoti Ranjan Mishra; Anshu Lata (Indian Journal of Extension Education, 2023)
The entrepreneurial climate is a set of tangible and intangible factors that shape and create a climate for agripreneurship in a region or area. An attitude scale was developed with 44 items (36 items positive and 8 negatives) during 2022. It was administered to 120 agripreneurs of Uttar Pradesh and it was found that the majority of the factors namely institutional, psychological, cognitive, sociological, economical, and managerial were contributing significantly to creating and shaping the entrepreneurial climate. Among these major factors, managerial factors were contributing most prominently with the highest total mean score of 2.83. The possible relation between socio-personal, socio-psychological, and entrepreneurial variables was explored considering the various dimensions of entrepreneurial climate as dependent variables. It was found that the majority of characteristics was associated with entrepreneurial climate and was able to define to the extent of 62.30%.